Adição de superplastificante e anti-segregante à base de CMC em pastas de cimento para Poços de Petróleo - Jacinto, Túlio Wágner Batista (2008)
Oil well cementing materials consist of slurries of Special class Portland cement dispersed in water. Admixtures can be used to provide the necessary fluidity, so the material can be efficiently pumped down as well as penetrate porous rocks with controlled filter loss. Construction admixtures can be used to modify the properties of oil well cements provided they can withstand and hold their properties at the higher than ambient temperatures usually encountered in oil fields. In civil construction, superplasticizer play the role of dispersants that reduce the facto r of water cement improve mechanical properties and fluidity of the cement, whereas anti-segregation agents improve the workability of the slurry. In the present study, oil well cement slurries were produced adding both a dispersant and an anti-segregation agent conventionally used in Portland CPII-Z-32 RS cement aiming at materials for primary cementing and squeeze operations. Three basic aspects were evaluated: fluidity, filter loss and the synergetic effect of the admixtures at two temperatures, i.e., 27°C and 56°C, following API RP 10B practical recommendations. The slurries were prepared using admixture concentrations varying from 2.60 Kgf/m3 (0.02 gallft3) to 5.82 Kgf/m3 (0.045 galJft3) BWOC. The density of the slurries was set to 1.89 g/cm3 (15.8 Ib/gal). 0.30 to 0.60% BWOC of a CMC-based anti-segregation agent was added to the cement to control the filter loss. The results showed that the addition of anti-segregation at concentrations above 0.55% by weight of cement resulted in the increased viscosity of the folders in temperatures evaluated. The increasing the temperature of the tests led to a reduction in the performance of anti-segregation. At concentrations of 5.20 kgf/m3 (0,040 gallft3) and 5.82 Kgf/m3 (0,045 gal/ft 3) observed a better performance of the properties evaluated in the proposed system. At low temperature was observed instability in the readings of rheology for all concentrations of anti-segregation. Contents that increasing the concentration of anti¬-segregation is limited concentrations greater than 0.55 % BWOC of the CMC in temperature analyzed. The use of the system with CMC promoted a good performance against the properties evaluated. The principal function of anti¬-segregation was optimized with increasing concentration of superplasticizer, at temperatures above the 2rC. The study of the behaviour of systemic additives, resulting in slurries of cement, which can be optimized face studies of other intrinsic properties in oil fields